2021
DOI: 10.19181/inter.2021.13.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Conducting Interviews during the COVID-19 Pandemic and Beyond

Abstract: The use of telephone and VoIP (Voice over Internet Protocol) interviews has become necessary owing to the legal restrictions and safety measures introduced during the COVID-19 pandemic. This has furthered scholarly dialogue surrounding the choice of interview mode, and the assumption that face-to-face interviews are the "gold standard" [Novick, 2008: 397]. The general public has also become more accustomed to utilising VoIP in their day-to-day lives. In this article, I discuss this change in communication meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Several studies have reported that ASHAs are unhappy with the present incentive-based honorariums and are seeking permanent jobs with salaries [ 22 , 24 ]. Non-availability of transport has been described in other studies [ 19 , 25 ], for example, emergency “108” vehicles were often delayed in Orissa [ 25 ]).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Several studies have reported that ASHAs are unhappy with the present incentive-based honorariums and are seeking permanent jobs with salaries [ 22 , 24 ]. Non-availability of transport has been described in other studies [ 19 , 25 ], for example, emergency “108” vehicles were often delayed in Orissa [ 25 ]).…”
Section: Discussionmentioning
confidence: 80%
“…Two researchers (a qualitative researcher and an epidemiologist/health scientist) conducted in-depth face-to-face interviews in the pre-COVID-19 study. The interviews undertaken during the COVID-19 pandemic were conducted and audio-recorded over the telephone (to comply with social distancing regulations) [ 19 ] by MG, a female anthropologist who analysed the data for both studies. The interviews took place in the evenings, when the participants could dedicate sufficient time and were not constrained by work obligations, and lasted from 60 to 90 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…Each interview lasted between 50 and 120 minutes. Interviews were primarily conducted in person; however, others took place online (via Microsoft Teams or Zoom) when necessary or requested (Self, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Our goal is to share our approach and key learnings with others who wish to undertake body mapping in this way. Further, we seek to contribute to an emerging body of literature that explores the process of conducting research during the pandemic (see for example, Hill et al, 2021; Leese et al, 2022; Self, 2021; Vaughan et al, 2022).…”
Section: Background: Covid-19 and The Move To Body Mapping Onlinementioning
confidence: 99%